Determination of the minimal erythema dose for ultraviolet A1 radiation. (8th June 2017) - Gambichler, T.; Majert, J.; Pljakic, A.; Rooms, I.; Wolf, P.
Summary: Background: There is limited knowledge of the potential of ultraviolet A1 (UVA1) radiation to induce erythema. Objectives: To investigate the minimal erythema dose (MED) for UVA1 in a German and Austrian population and to determine UVA1 dose–response curves for erythema and pigmentation. Methods: We determined the UVA1‐MED in 59 participants using a geometric increase in the dose. Visual readings of erythema and pigmentation were performed at 10 min, 2 h and 24 h after the UVA1 irradiation. Colorimetric measurements were taken to determine erythema (a* value) and pigmentation (L* value) objectively. Results: More than 30% (18 of 59) of the participants had a high‐dose UVA1‐MED (> 70–130 J cm −2 ); 56% (33) had no detectable UVA1‐MED after 24 h and eight (14%) had a medium‐dose UVA1‐MED (20–70 J cm −2 ). We observed a stepwise decrease of the a* value measured at the UVA1‐MED skin site from 10 min to 2 h and 24 h ( P < 0·001). In contrast, there was a stepwise increase of the L* value measured at the UVA1‐MED skin site from 10 min to 2 h and 24 h ( P < 0·001). Conclusions: Most participants had no measurable UVA1‐MED even after commencing high doses such as 130 J cm −2 . Only a minority of participants (14%) may develop UVA1‐induced erythema in the low‐ and medium‐dose region. Hence, it appears to be safe to start UVA1 phototherapy with 20 J cm −2 of UVA1 and continue with subsequent daily dose increments of 10 J cm −2, up to the desired maximum dose. Abstract : What's already known about this topic? Ultraviolet A1 (UVA1) is a well‐established phototherapeutic option for many skin conditions. Although UVA1 is frequently used in relatively high‐dosage regimens, knowledge on the occurrence of UVA1‐induced erythema is very limited. What does this study add? Most participants with skin phototypes II to IV did not show UVA1‐induced erythema at 24 h even after commencing high doses such as 130 J cm −2 A minority of participants developed UVA1‐induced erythema, even within the low‐ and medium‐dose region 24 h after exposure. Respond to this article Linked Comment: Calzavara‐Pinton and Caravello. Br J Dermatol 2017;177 :19–20 Plain language summary available online